Controlling Well Leakage: Rheological and Operational Effects (Annual Transactions of the Nordic Rheology Society, 2024)
Many hydrocarbon wells leak gas, due to shrinkage and other microannuli that typically form along the cement-casing and cement-formation interfaces. These microannuli are variable due to irregularities in the primary cementing process and other operational anomalies. Repair of such defects is via a process called squeeze cementing, that involves pumping a thin cement slurry into the microannulus under pressure. Trudel & Frigaard1 developed a stochastic model of well leakage able to predict all but extreme (high and low) rates of leakage for a median well in British Columbia (BC), Canada, benchmarked against leakage rates observed in 2010-2019. Izadi et al.2,3 have explored the effects of pumping (yield stress) slurries into these narrow irregular geometries, using a Monte-Carlo approach to account for the extreme variability. This enabled us to give probabilistic predictions of the likely effects of the squeeze cementing operation. Here we extend our analysis to different operational scenarios, showing how rheological effects can influence repair of the microannulus.